Ruiša pūķgalve Latvijas Universitātes Muzeja herbārijā - Jamonte, Daiga (My University, 2020)
Par Gada augu 2020 tika izvēlēts Latvijas aizsargājamais augs ruiša pūķgalve, ko Latvijā pirmo reizi atradis dabaspētnieks Eduards Lēmanis (1841 – 1902) 1883. gadā Antonopolē. Tas kopā ar citiem ruiša pūķgalves herbārija paraugiem glabājas Latvijas Universitātes Muzeja Botānikas un mikoloģijas kolekcijās. Tie ir gan Latvijā, gan Igaunijā ievākti eksemplāri laika posmā no 1848. līdz 1977. gadam.

The Plant of the year 2020 was the Latvian protected plant northern Dragon-head, which was first found in Latvia by naturalist Eduards Lēmanis (1841 - 1902) in 1883 in Antonopolis. It is stored in the Botanical and mycological Collections of the Museum of the University of Latvia together with other specimens of the northern Dragon-head herbarium. These are specimens collected in both Latvia and Estonia in the period from 1848 to 1977.
Northern Dragon-head in the herbarium of the Museum of the University of Latvia
Keywords: ruiša pūķgalve; northern Dragon-head; Eduards Lēmanis; Antonopole; Numerne; Herbarium Latvicum (RIG II); Herbarium Balticum (RIG I); Research Subject Categories::NATURAL SCIENCES::Biology; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of science